The impact of the covid-19 pandemic on pediatric mental health emergency - YILDIRIM, ALPER (My University, 2023)
© 2023, AVES. All rights reserved.Objective: The aim of this study was to compare pre/post-coronavirus disease 2019 pandemic changes in mental health-related visits to the pediatric emergency department. Materials and Methods: We conducted a retrospective analysis of all mental health-related pediatric emergency department visits to a tertiary general hospital between June and September 2019, 2020, and 2021. We described pre/post-coronavirus disease 2019 changes in the use of pediatric emergency departments, such as timing of visits, sex discrepancies, diag-nostic distribution, discharge planning, and others. Results: Compared with the corresponding months before the pandemic (n = 187), mental health-related pediatric emergency department visits decreased by 20.8% in June–September 2020 (n = 148) and increased by 12.2% in 2021 (n = 210). The distributions of age, sex, timing of visits, reasons for presentations, hospitalization, and outpatient clinic appointment rates were not statistically significant between the years. Self-harm in females and aggression/violence in males were the most common reasons for presentation to pediatric emergency departments in each year. In the post-pandemic period, ambulance use and patients referred by other hospitals for psychiatric consultation increased, while the completion time of consultations decreased (P <.05). The frequency of attention-deficit hyperactivity disorder and depression decreased, but obsessive-compulsive disorder and anxiety disorders were more common in the post-pandemic period than in the corresponding months before the pandemic (P <.05). Conclusion: Our results suggest that the coronavirus disease 2019 pandemic resulted in a significant change in mental health-related visits to the pediatric emergency department. Those in the groups with reduced visits may be at risk for delayed access to treatment for their mental and behavioral difficulties.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Health Sciences; Klinik Tıp (MED); Klinik Tıp; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics, Perinatology and Child Health; Adolescent; depression; emergency; mental health; pandemi; Adolescent; depression; emergency; mental health; pandemic